2009
DOI: 10.1007/s12665-009-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity tomography mapping of beachrocks: application to the island of Thassos (N. Greece)

Abstract: Electrical resistivity tomography (ERT) technique is widely used in mapping subsurface electrical properties. In this study, ERT was used to map a beachrock outcrop, extended both inland, under beach sediments, and seawards, on and under seafloor sediments. Mapping of beachrock is considered important because it can help evaluate the lateral and vertical extend of the formation. Fast and reliable mapping of beachrocks may contribute in several applications like engineering and construction, coastal management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 23 publications
2
5
0
1
Order By: Relevance
“…These velocity layers and resistivity layers were thought to capture the vertical distribution of beachrocks, and the thickness of the beachrocks was estimated to be a maximum of 1 m. In particular, the high resistivity layer in the surface layer at a distance of 3 to 44 m from line-2 corresponded to the beachrock distribution area, where the electrode could only be driven in by about 2 cm. This resistivity layer was almost consistent with that of the beachrock shown by David [4], who reported a resistivity of 2-15 Ωm and a 1-m thickness and Kubo et al [5], who reported a resistivity of 4-20 Ωm and 1-m thickness. A section with high resistivity (46.6 to 78.7 Ωm) was also observed at a distance of 17 to 33 m of the survey line-2, but this can be assumed to correspond to a dry beachrock layer on the ground surface.…”
Section: Geophysics Measurementsupporting
confidence: 88%
See 1 more Smart Citation
“…These velocity layers and resistivity layers were thought to capture the vertical distribution of beachrocks, and the thickness of the beachrocks was estimated to be a maximum of 1 m. In particular, the high resistivity layer in the surface layer at a distance of 3 to 44 m from line-2 corresponded to the beachrock distribution area, where the electrode could only be driven in by about 2 cm. This resistivity layer was almost consistent with that of the beachrock shown by David [4], who reported a resistivity of 2-15 Ωm and a 1-m thickness and Kubo et al [5], who reported a resistivity of 4-20 Ωm and 1-m thickness. A section with high resistivity (46.6 to 78.7 Ωm) was also observed at a distance of 17 to 33 m of the survey line-2, but this can be assumed to correspond to a dry beachrock layer on the ground surface.…”
Section: Geophysics Measurementsupporting
confidence: 88%
“…Most of the research on beachrock is related to its geological or chemical properties, and there is very little literature on the underground structure of beachrock. There have been a few cases of electrical exploration on Thassos Island, Greece [4]. To elucidate the formation process of beachrock, it is important to understand the structure of its underground and surrounding area.…”
Section: Introductionmentioning
confidence: 99%
“…The resistivity of the beachrock on the island of Thassos, Greece, is about 215 ³m according to Psomiadis, 12) whereas that on Yagaji island, Japan, is about 416 ³m (Fig. 6).…”
Section: Characteristics Of the Beachrock At The Study Sitementioning
confidence: 99%
“…In particular, its underground structure is not yet well understood. One of the few studies of this was by Psomiadis, 12) who used electrical resistivity tomography to map the beachrock on the island of Thassos, Greece. In spite of the general claim that comprehending the underground structure of beachrock is absolutely imperative to elucidating its formation mechanism, research has been restricted to areas near the surface at the seashore because of concerns about damaging the landscape with exploratory boring.…”
Section: )mentioning
confidence: 99%
“…1). The beach is 375 m long and reaches width of 25 m (Psomiadis et al, 2009a). Coastal sediments are fine to medium well graded sand with some gravels on the south side where a stream is discharging.…”
Section: Setting Of the Study Areamentioning
confidence: 99%